2022
DOI: 10.1155/2022/1455025
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Changes in the Heart Rate Variability of Patients Undergoing Coronary Artery Bypass Grafting Surgery

Abstract: Introduction. Coronary artery bypass grafting (CABG) with extracorporeal circulation is a key therapy for coronary artery disease (CAD). However, cardiovascular events and cardiac arrhythmias may still occur in these patients following surgery. Many studies have demonstrated a correlation between cardiac arrhythmias and heart rate variability (HRV). This study aimed to establish the temporal change pattern of HRV observed following CABG. Methods. A prospective method was used to study 119 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…CABG surgery patients were less nervous preoperatively than valve surgery patients. CABG patients had greater anxiety levels in other trials [18]. Using the conventional analgesia procedure, moderate to severe anxiety patients had greater postoperative pain ratings than mild anxiety patients in the first 24 hours.…”
Section: Discussionmentioning
confidence: 86%
“…CABG surgery patients were less nervous preoperatively than valve surgery patients. CABG patients had greater anxiety levels in other trials [18]. Using the conventional analgesia procedure, moderate to severe anxiety patients had greater postoperative pain ratings than mild anxiety patients in the first 24 hours.…”
Section: Discussionmentioning
confidence: 86%
“…Published studies of the short-term changes in HRV post-CABG are listed in Table 4 (Ref. [ 18 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]). In addition, some of these studies recorded HRV changes beyond 6 weeks post-CABG, these results are discussed in the section following this one.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported a decrease in traditional HRV parameters immediately after surgery, reaching their lowest value at 3–6 days post-CABG and remaining depressed even 6-weeks follow up after surgery [ 24 , 25 , 26 , 27 , 28 , 29 ]. Thanh et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations